Pathological Manifestations and Damage Mapping of a Historical Building: Case Study of the Church of Nossa Senhora do Pilar in Recife, Brazil - Rodrigues, Stephany Rayane Silva; Lins , Lívia Campos; Soares , Willames de Albuquerque; Monteiro, Eliana Cristina Barreto (Scientific Journal ANAP, 2025)
Objective – To contribute to the conservation of cultural memory and the preservation of built historical heritage through the analysis of pathological manifestations in a historical building listed by IPHAN, the Church of Nossa Senhora do Pilar. Methodology – The analysis was carried out through data collection, visual inspection, mapping of pathological manifestations, graphical representation using a damage map, and qualitative and quantitative analysis of the anomalies observed on the building’s façades, by measuring the total damage coverage and the Damage Factor. Originality/Relevance – Application of a methodology for the analysis of pathological manifestations in built historical heritage in both qualitative and quantitative terms, enabling data comparison and providing greater support for decision-making in conservation management, thus contributing to material preservation and the dissemination of cultural and emotional memory, by documenting its current condition and providing a basis for maintenance actions. Results – The findings show that this building is vulnerable to external damage, especially on the South (front) and North (rear) façades. According to qualitative and quantitative analyses, the most frequently observed pathological manifestations are, in descending order: dirt/biofilm, moisture, and improper interventions, which can compromise the durability of elements and the historical value of the construction. Theoretical/Methodological Contributions – The research highlights the importance of using the damage map for diagnosing pathological manifestations and the relevance of quantitative analysis, which enables the comparison of information between façades and with data from other buildings, making it a useful tool to support conservation management. Social and Environmental Contributions – The study contributes to the preservation of built historical heritage by guiding maintenance actions, which enhance the durability of the asset and promote its use by the public, potentially attracting financial resources through tourism. Furthermore, restoration is a strong ally of sustainability, as it extends the lifespan of constructions while maintaining their historical value and relevance.